Smallholder Irrigation Schemes, Agrarian Reform and 'Accumulation from Above and from Below' in South Africa. (12th December 2012) - Cousins, Ben
<x xml:space="preserve">Abstract</x> A key issue in debates on agrarian reform in South Africa is the potential for small‐scale farming, in conjunction with redistributive land reform, to make a significant contribution to employment creation and poverty reduction. Two problems hinder these debates – the paucity of reliable data on small‐scale agriculture, and lack of clarity on the meaning of terms such as 'smallholder' and 'small‐scale farmer'. This paper applies class‐analytic perspectives on social differentiation to critically examine these terms, and explores the prospects for 'accumulation from above and from below' through agrarian reform, drawing on wider debates within the Southern African region. It focuses in particular on smallholder irrigation schemes, potentially a key focus of policy, and presents research findings on production and marketing of fresh produce in one such scheme in Tugela Ferry, KwaZulu‐Natal. Survey data show that farming households combine agriculture and various forms of off‐farm labour, as is often the case throughout the region, and that accumulation in small‐scale agriculture is constrained by a number of factors, including the inherited and largely untransformed agrarian class structure of South Africa. In this context, expanded access to land and water is a necessary but not sufficient condition for such accumulation; wider structural change is also required.